Can Self-commodification occur in the Digital space? Viewing the Use of Dating Apps Through the Lens of Commodification and Consumerism - Valente, V.; Vieira, Jorge (XIII Congresso Português de Sociologia, 2025)
Can self-commodification occur in a digital space? This question invites a critical debate on the concept of commodification and its intersection with consumer culture, using dating apps as an object that may embody both. This communication does not seek to provide conclusive answers to whether dating apps or their use are inherently commodifying, or not. Instead, this comes as a proposal for further discussion of commodification and self-presentation within the scope of consumer culture. Through various theoretical lenses, each refracted through its own prism, we will explore how the different stages of utilizing a dating app may contribute, or not, to the commodification of the self. The aim is to lean on Featherstone’s (1991) three perspectives on consumer culture, Goffman’s (1956) Theory of Presentation of Self, and Marx’s (1915) concept of commodity fetishism to explore the potential connection between consumerist culture and intimate social interactions, positing that dating apps may play a role in reinforcing consumerist behaviors. Dating apps provide users access to a pool of people who are interested in forging new relationships. The process of utilizing a dating app culminates in three stages. The first is the registration and creation of the profile. In this stage, users select several pictures and write a text of established length according to the dating app’s guidelines, describing themselves and what they look for. The second stage includes the selection period, in which a user will be presented with other profiles to select from based on their interest. The third stage occurs when there is mutual interest and both users “match.” From this point, users may be able to interact via chat. This process suggests that even personal relationships are subject to the same fast-paced, transactional logic that shapes consumer behavior. Personal identities are curated, marketed, and consumed. The profile creation stage, where self-presentation is central, involves carefully crafting and promoting one’s image as an appealing and interesting potential partner. During the selection and matching stages, users hypothetically “consume” the profiles they encounter, seeking not just a match, but often the “better” match. Such reflection poses important questions about what this means for how we understand identity and intimacy today. Do these platforms support meaningful relationships or push people toward treating each other as consumable items? While dating apps make finding connections easier, they also risk promoting shallow interactions based on instant appeal, raising concerns about whether they’re commercializing love and personal connections. By encouraging reflection on how technology influences not just what we buy but how we form relationships, this study invites sociologists to consider the broader effects of commodification in digital dating spaces.